Analisis Kegiatan Arisan Dalam Perspektif Islam Di Kelurahan Sememi Surabaya - Putri, Adila Rachmaniar; Suryaningsih, Sri Abidah (Universitas Negeri Surabaya, 2018)
Arisan is an activity that is often held by the community, which many of it are Muslims. Arisan activity is also an economic activity that contains akad-akad (Islamic legal contract) in it. So the purpose of this study is to examine the activities of arisan in Sememi Surabaya in the perspective of Islam.This research uses descriptive qualitative method that aims to understand the activity of arisan in Sememi Surabaya. From the results of the research it can be summarized that the trading activities in the Village Sememi do not form any association, and the arisan itself still contains elements of usury from